Ecological risk assessment of heavy metal pollutants and total petroleum hydrocarbons in sediments of the Bohai Sea, China. (November 2022) - Wei, Yuqiu; Ding, Dongsheng; Qu, Keming; Sun, Jun; Cui, Zhengguo
Abstract: Heavy metals and organic pollutants like total petroleum hydrocarbons (TPHs) in coastal marine sediments are receiving extensive attention, as they may pose a serious threat to the aquatic environment and ecosystem health. To date, however, data on the long-term variations in the levels of sedimentary heavy metals and TPHs as well as their ecological risks are relatively limited. Here, we conducted 12 cruises spanning 3 years in the Bohai Sea and obtained ~1400 sediment samples to explore the long-term variations of heavy metals (i.e., Hg, As, Cu, Zn, Pb, Cd) and TPHs, and to assess their potential ecological risks. The results suggested that the ranges for the levels of Hg, As, Cu, Zn, Pb, Cd, and TPHs in sediments between 2019 and 2021 were <0.01–0.07, 0.23–10.72, 8.07–20.67, 25.52–46.55, 10.94–28.19, 0.14–0.56, and 9.14–18.41 mg kg −1, respectively. Based on the single factor evaluation ( F i ) for sediment quality, we found that most of the evaluation factors in the study area met the requirements of sediment quality standard (i.e., F i  < 1), except for the factor of metal Cd in some cases. The implication is that the sediment in the Bohai Sea was fairly clean in terms of heavy metals and TPHs. However, the concentration of metal Cd exceeded the sediment quality standard during May 2019 and 2020 (i.e., F i  > 1), indicating that Cd could be identified as a major pollutant in surface sediments. Also, based on the ecological risk assessment ( E i ) of heavy metal pollutants, we found that the metal Cd had reached a level with potential ecological risk in some cases (80 ≤  E i  < 160). As such, we further suggested that the Cd contamination might have a potential risk on the Bohai Sea' ecosystem. Highlights: The Bohai Sea was fairly clean in terms of heavy metals and TPHs. Cd could be identified as a major pollutant in surface sediments. The Cd contamination might have a potential risk on the Bohai Sea' ecosystem.